Translating Chinese Comics Titles into the Thai Language - Kullayanee Kittopakarnkit; Phongpitch Sawongram (My University, 2022)
Comics have been a popular entertainment medium throughout the years. The Chinese cartoon has developed continuously since the late 19 century to early 20 century, imported into Thailand both in book form and online from around 2000, and has been translated into the Thai language for Thai readers. The translation of a comic's title has a profound impact in terms of attracting readers to that particular comic. This research is to study the translation of Chinese comics titles into Thai language. The objective is to study strategies for translation problems and solutions to problems arising from such translations. According to the research results, it was found that the giving titles method using the source language as a conductor of transmission was the most popular. The least popular method is giving titles by dynamic transmission.
Keywords: Translation Studies and Practices